FRI0169 Cyclosporin a versus Ýnterferon alfa in treatment of severe ocular involvement of behÇet's disease. (1st June 2001) - Dýnc, A; Pay, S; Bayraktar, Z; Erdem, H; Turan, M
Abstract : Background: Sight-threatening uveitis is a well-known complication of Behçet's Disease in which recurrent oral and genital aphthous ulcerations, arthritis, neurologic, and vascular involvement also frequently accompanied. Objectives: In this study we compared the clinical efficacy of cyclosporin A (Cyc-A) and interferon-alfa (INF-alfa) in our patients with severe posterior uveitis. Methods: All patients were classified and followed by means of fundus fluoressein angiography. At baseline, Cyc-A and INF-alfa were given in a dose of 5 mg/kg/day and 4, 5 million U three times a week, respectively. In case of an attack, a prednison treatment course was added those monotherapy regimen. Twenty-one patients were included in the study. Eight and eleven patients were started on Cyc-A and INF-alfa regimens, respectively. Here, the results at the 3- and 6-month duration were presented. Results: Two of 8 patients treated with Cyc-A were stopped to continue due to inefficacy and switched on INF-alpha therapy. In the same group one patient had gingival hyperplasia, which partially responded to dose tapering, however another patient with azotemia and hypertension had to be changed to other treatment group. Except one, all patients on INF-alpha regimen completed the study with adequate regression of inflammatory activity. In that patient depression unresponsive to drugs leaded to stop INF-alpha at the end of 6 months. Conclusion: Although it is difficult to make a clear conclusion about the comperative efficacy of INF-alpha and Cyc-A due to small population and short follow-up. But it seems that INF-alfa more tolerable than Cyc-A in the treatment of Behçet' Disease with severe ocular involvement.